Optimizing humidification–dehumidification desalination systems: Impact of nozzle position and geometric configuration on performance and efficiency - Mohammad Alrbai; Ahmad Al Masri; Dareen Makawii; Ali Alahmer (International Journal of Thermofluids)
The humidification-dehumidification (HDH) desalination system is an effective solution for sustainable water production due to its low energy consumption and minimal environmental impact. This study explores the performance optimization of HDH systems by analyzing nozzle positioning, geometric configurations, and thermodynamic efficiency. Furthermore, the study compares bottom-nozzle and top-nozzle configurations in both the humidifier and dehumidifier units to evaluate their impact on heat transfer, moisture absorption, and water recovery. Computational Fluid Dynamics (CFD) simulations in ANSYS Fluent® were employed to model fluid dynamics, heat, and mass transfer, while the Discrete Phase Model (DPM) simulated water jet nozzle injections. Thermodynamic and exergy analyses using MATLAB® evaluated entropy changes and system efficiency. The results reveal that a bottom-nozzle configuration in both the humidifier and dehumidifier enhances performance, achieving a 4.34% humidity ratio compared to 3.25% with the top-nozzle setup. The dehumidifier demonstrated superior efficiency, with a Gain Output Ratio (GOR) that reached 7.2. Geometric analyses revealed that cylindrical designs reduced head loss by 8%, from 4.91 mm in square prisms to 4.45 mm, while improving turbulent flow and heat and mass transfer through better air-water interaction. Exergy efficiency for the humidifier was approximately 14%, highlighting the importance of optimal configurations. These results emphasize the significance of nozzle placement and geometric design in enhancing the efficiency of HDH desalination systems.